PERAN HEALING ENVIRONMENT PADA INTERIOR INSTALASI RAWAT INAP VIP IBU DI RSIA - Aspirani, Melva; Hadiansyah, Mahendra Nur; Haristianti, Vika (Program Studi Desain Interior Unikom, 2020)
According to Statistic of Bandung City in 2018, the number of women in the fertile period (15-49 years) has increased from the previous year (2017) of 108.816 people. Thats has an effect on the increasing use of inpatient rooms at women and children hospital. Pregnant and postpartum patients have different emotional and behavioral stability. Uncomfortable inpatient conditions will affect the healing process of the patients apart from the aspect of medical treatment. The solution to this problem is to use the concept of Healing environment. Thia article aims to examine the role of healing environment in achieving comfort in the impatient rooms at women and children hospital. Methods of research that has been done is qualitative. The analysis was performed with observation of application of healing environment’s principles at RSIA Limijati Bandung, RSAB Harapan Kita West Jakarta, and Kemang Medical Care South Jakarta. The result of observation then will assess and used as a guide of the design process. Hoped this article can inspire interior designer to create of impatient rooms in accordance with patient psychology to create rooms comfort for patient.